PENGARUH MODAL PSIKOLOGIS DAN PARTISIPASI ANGGARAN TERHADAP KEINGINAN UNTUK MEMBUAT SENJANGAN ANGGARAN - Jengger Woro Hapsari; Alwi Alwi (LPPM Universitas Bina Insan, 2020)
The study aimed at finding out the effect of psychological capital dan budgetary participation on the budgetary slack. The population are all of Kopertis in the Indonesia. There were about 84 respondents are budgetary team in Kopertis. The data were collected by using five instrument of questionnaries based on Likert-scales. Data quality test was made by using validity and reability. The hypotesis is tested using hypotesis T-Test. From the results of hypotesis tests it is concluded that (1) there was affect of psychological capital on the budgetary slack (2) there was not affect of budgetary participation on the budgetary slack.